Intersectionality in probation: examining gender and race disparities in probation conditions and sentence length - Shaw, Olivia (Journal of ethnicity in criminal justice, 2024)
This article uses the focal concern perspective to examine how extralegal factors like race, ethnicity, and gender affect probation outcomes and length. Utilizing a representative sample from Florida, the study employs cross-sectional regression analyses, including multinomial and ordinary least squares (OLS) models. Interaction effects are modeled to highlight the role of intersectionality in probation decisions. Results from this study reveal that gender and race disparities exist in the assignment of probation conditions and sentence length. Policy implications address judicial decision-making, disparities, and length of stay on probation.